Salivary Gland Pleomorphic Adenomas Presenting With Extremely Varied Clinical Courses. A Single Institution Case-Control Study† - Piwowarczyk, Krzysztof; Bartkowiak, Ewelina; Kosikowski, Paweł; Chou, Jadzia Tin-Tsen; Wierzbicka, Małgorzata (Frontiers in Oncology, 2021)
Objective: Pleomorphic adenomas (PAs) with divergent clinical behavior, differing from the vast majority of PAs, were distinguished. “Fast” PAs are characterized by an unexpectedly short medical history and relatively rapid growth. The reference group consisted is constituted of “slow” PAs with very stable biology and long-term progression. We divide the PA group as a whole into three subsets: “fast”, “normal” and “slow” tumors. Our goal is a multifactorial analysis of the “fast” and “slow” PA subgroups. Methods: Consecutive surgeries in a tertiary referral center, the Department of Otolaryngology and Laryngological Surgery, Poznan University of Medical Sciences, Poland, were carried out between 2002 and 2011. Out of 1154 parotid tumors, 636 (55.1%) were PAs. The data were collected prospectively in collaboration with the Polish National Registry of Benign Salivary Gland Tumors. The main outcome measure was the recurrence rate in “fast” and “slow” PA subgroups. All surgery surgical qualifications and surgeries were performed by two experienced surgeons. Results: Slow PAs, compared to fast PAs, presented in older patients (53.25±15.29 versus 47.92±13.44 years). Multifactor logistic regression analysis with recurrence (yes/no) as the outcome variable, fast/slow as the predictor variable and age, gender, margin, FN status as covariates showed that fast PAs were significantly predicting recurrence vs. slow PAs (p=0.035). Fast PAs were increasing the risk of PAs 10-fold vs. slow PAs, exp β = 10.20, CI95 [1.66; 197.87]. The variables impacting relapse were: recent accelerated growth of the tumor OR=3.35 (SE=0.56), p=0.030, positive margins OR=7.18 (SE=0.57), p<0.001, incomplete or bare capsule OR=9.91 (SE=0.53), p=0.001 and location III OR=3.12 (SE=0.53), p=0.033. In the multivariate model only positive margin was selected as the best predictor of relapse, OR=5.01 (SE=0.60), p=0.007. Conclusions: The simple clinical aspect of slow or fast PA progression is of great practical importance and can constitute a surrogate of the final histopathological information that is derived from the surgical specimen. The slow or fast nature of the PA to some extent indicates prognostic features such as recurrence risk. This finding requires correlation with histological and molecular features in further stages of research.